Prospectively Recorded versus Medical Record‐Derived Spinal Cord Injury Scores in Dogs with Intervertebral Disk Herniation. (26th July 2013) - Van Wie, E.Y.; Fosgate, G.T.; Mankin, J.M.; Jeffery, N.D.; Kerwin, S.C.; Levine, G.J.; Greatting, H.H.; Chen, A.V.; Barker, A.K.; Levine, J.M.
Abstract : Background: Validated spinal cord injury (SCI) scores have been established for veterinary species but are not uniformly used in practice. Hypothesis/objectives: To determine the level of agreement of SCI scores at the time of admission versus those assigned from reconstructed medical records in a population of dogs with intervertebral disk herniation (IVDH). Animals: Eighty‐six client‐owned dogs with confirmed IVDH. Methods: Retrospective study. Medical records were reviewed for history, physical examination, neurologic examination, and recorded Modified Frankel score (MFS) and Texas spinal cord injury score (TSCIS) at the time of admission. Three raters, all board‐certified neurologists, assigned MFS and TSCIS based on digitized abstracted medical records to each patient. These scores were then compared to the recorded score at the time of admission. Results: Actual agreement for MFS and TSCIS derived from medical records by the 3 raters compared to prospectively derived MFS and TSCIS was 77.9 and 51.2%, respectively. A kappa value of 0.572 (95% CI 0.450, 0.694; P  < .001) and an ICC of 0.533 (95% CI 0.410, 0.646; P  < .001) were calculated for MFS scores. A kappa value of 0.100 (95% CI 0.000, 0.222; P  = .107), and an ICC of 0.503 (95% CI 0.377, 0.620; P  < .001) were calculated for TSCIS scores. Conclusions and Clinical Importance: Results showed that SCI scores recorded at the time of admission often do not agree with those retrospectively abstracted from medical records. Agreement was less when using the more complex TSCIS scale and therefore the MFS scale might be more appropriate for use in retrospective studies.